(untitled) (Anclajes, 2024)
Autobiographical writings with homoerotic content have constantly reflected the struggles between dissident identities and heteronormative systems. The case of Antes que anochezca (1992) by Reinaldo Arenas is no exception. Therefore, the hypothesis of this analysis states that the pride of the hypersexualized dissident subject –in this case, an autobiographical subject– appears as a tool of normative destabilization in the face of sex-gender systems that promote heteropatriarchal masculinity and sexuality. Consequently, Arenas’ speech incites a rereading of the body to dismantle it from the bonds imposed by the devices of power –especially that which corresponds to the idea of ​​the “hombre nuevo” emanating from the Cuban Revolution–. It also traces the representation of a dissident subject that does not adhere to the ideology of the global North, but rather to a vision adhered to the system of Mediterranean desire, governed by the sexual dichotomy of the active/passive axis.